IDNLearn.com: Where curiosity meets clarity and questions find their answers. Get the information you need from our community of experts who provide accurate and comprehensive answers to all your questions.
Sagot :
Certainly! Let's work through the problem step by step.
The function given is [tex]\( h(x) = 6 - x \)[/tex].
1. First, apply the function [tex]\( h \)[/tex] to the number 10. This is denoted as [tex]\( h(10) \)[/tex]:
[tex]\[ h(10) = 6 - 10 = -4 \][/tex]
2. Next, we need to find [tex]\( (h \circ h)(10) \)[/tex], which means we need to apply the function [tex]\( h \)[/tex] to the result of [tex]\( h(10) \)[/tex]. In other words, we need to find [tex]\( h(h(10)) \)[/tex]:
- We already found that [tex]\( h(10) = -4 \)[/tex], so now we need to find [tex]\( h(-4) \)[/tex]:
[tex]\[ h(-4) = 6 - (-4) = 6 + 4 = 10 \][/tex]
So the value of [tex]\( (h \circ h)(10) \)[/tex] is [tex]\( 10 \)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{10} \][/tex]
The function given is [tex]\( h(x) = 6 - x \)[/tex].
1. First, apply the function [tex]\( h \)[/tex] to the number 10. This is denoted as [tex]\( h(10) \)[/tex]:
[tex]\[ h(10) = 6 - 10 = -4 \][/tex]
2. Next, we need to find [tex]\( (h \circ h)(10) \)[/tex], which means we need to apply the function [tex]\( h \)[/tex] to the result of [tex]\( h(10) \)[/tex]. In other words, we need to find [tex]\( h(h(10)) \)[/tex]:
- We already found that [tex]\( h(10) = -4 \)[/tex], so now we need to find [tex]\( h(-4) \)[/tex]:
[tex]\[ h(-4) = 6 - (-4) = 6 + 4 = 10 \][/tex]
So the value of [tex]\( (h \circ h)(10) \)[/tex] is [tex]\( 10 \)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{10} \][/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and come back for more insightful information.